Splicing of a non-coding antisense transcript controls LEF1 gene expression. Issue 12 (18th May 2015) - Beltran, Manuel; Aparicio-Prat, Estel; Mazzolini, Rocco; Millanes-Romero, Alba; Massó, Pere; Jenner, Richard G.; Díaz, Víctor M.; Peiró, Sandra; de Herreros, Antonio García
Abstract: In this report we have analyzed the role of antisense transcription in the control of LEF1 transcription factor expression. A natural antisense transcript (NAT) is transcribed from a promoter present in the first intron of LEF1 gene and undergoes splicing in mesenchymal cells. Although this locus is silent in epithelial cells, and neither NAT transcript nor LEF1 mRNA are expressed, in cell lines with an intermediate epithelial-mesenchymal phenotype presenting low LEF1 expression, the NAT is synthesized and remains unprocessed. Contrarily to the spliced NAT, this unspliced NAT down-regulates the main LEF1 promoter activity and attenuates LEF1 mRNA transcription. Unspliced LEF1 NAT interacts with LEF1 promoter and facilitates PRC2 binding to the LEF1 promoter and trimethylation of lysine 27 in histone 3. Expression of the spliced form of LEF1 NAT in trans prevents the action of unspliced NAT by competing for interaction with the promoter. Thus, these results indicate that LEF1 gene expression is attenuated by an antisense non-coding RNA and that this NAT function is regulated by the balance between its spliced and unspliced forms.